2007
DOI: 10.1007/s00705-007-0996-z
|View full text |Cite
|
Sign up to set email alerts
|

Unchanged high prevalence of antibodies to hepatitis E virus (HEV) and HEV RNA among blood donors with an elevated alanine aminotransferase level in Japan during 1991–2006

Abstract: Hepatitis E is rare in Japan but is occurring more frequently than previously thought. To investigate whether de novo subclinical infection of hepatitis E virus (HEV) has recently increased in Japan, HEV RNA was assayed in serum samples obtained from 4019 Japanese voluntary blood donors with alanine aminotransferase (ALT) of > or =61 IU/l, who are likely to have ongoing HEV infection, during 1991-2006. The overall rates of IgG-class antibody to HEV (anti-HEV IgG), anti-HEV IgM/IgA and HEV RNA among 3185 donors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 56 publications
3
36
1
1
Order By: Relevance
“…[1][2][3][4]8 Since the majority of HEV infections are subclinical, 10 17 Scotland 4.7%). 18 The rate of anti-HEV IgG seropositivity in the present study (21.1%) was considerably higher than the rates described above, [11][12][13][14][15][16][17][18] irrespective of ALT concentrations. The anti-HEV IgM seropositivity rates in the present study were 0.9% and 0.0% for donors with and without elevated ALT, respectively.…”
Section: Discussioncontrasting
confidence: 66%
“…[1][2][3][4]8 Since the majority of HEV infections are subclinical, 10 17 Scotland 4.7%). 18 The rate of anti-HEV IgG seropositivity in the present study (21.1%) was considerably higher than the rates described above, [11][12][13][14][15][16][17][18] irrespective of ALT concentrations. The anti-HEV IgM seropositivity rates in the present study were 0.9% and 0.0% for donors with and without elevated ALT, respectively.…”
Section: Discussioncontrasting
confidence: 66%
“…The seroprevalence rates observed in this study (donors with nonelevated ALT, 6%; donors with elevated ALT, 5.88%) are more comparable to rates which have been observed for Switzerland and Japan than to those observed for Germany so far. The seroprevalence rates of anti-HEV IgM have been measured less frequently, but studies in Chinese blood donors revealed a seroprevalence rate of 0.94 to 1.8% (11,21), comparable to 0.5 to 1.6% in Japan (18,20,42) and the 0.5% observed in this study. We also observed a considerably higher seroprevalence rate of 8.08% in donors with elevated ALT levels, according to data obtained by Fukuda et al (3.3%) (18).…”
Section: Discussionsupporting
confidence: 58%
“…The seroprevalence rates of anti-HEV IgM have been measured less frequently, but studies in Chinese blood donors revealed a seroprevalence rate of 0.94 to 1.8% (11,21), comparable to 0.5 to 1.6% in Japan (18,20,42) and the 0.5% observed in this study. We also observed a considerably higher seroprevalence rate of 8.08% in donors with elevated ALT levels, according to data obtained by Fukuda et al (3.3%) (18). However, comparison is rather difficult due to demographic differences in the study population and differences in the sensitivity of the commercially available assays used (27).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Retrospektive Untersuchungen von Spenden mit erhöhten Transaminasen (Untersuchungszeitraum 1991-2006) wiesen darauf hin, dass eine gleich bleibende Inzidenz von HEV-Infektionen bei japanischen Blutspendern zu beobachten war [175]. Nicht unerwartet ist, dass in den HEV-RNA-positiven Spenden die in Japan prävalenten Genotypen 3 und 4 nachweisbar waren.…”
Section: Prävalenz Und Inzidenz Bei Spenderkollektivenunclassified